A study of the factors which influence digital transformation in Kibs companies - Marino-Romero, Jorge Alberto; Palos-Sanchez, Pedro Ramiro; Velicia-Martin, Félix Antonio; Rodrigues, Ricardo Gouveia (Frontiers in Psychology, 2022)
Eighteen interviews were used in this research to inductively conceptualize the factors that influence digital transformation (DT) in Kibs companies that provide multidisciplinary Knowledge Intensive Business Services. Two main groups were identified: factors of DT and use in the new digital environment. Using the findings obtained, a comparison was made with the existing literature and the most relevant aspects of DT as a disruptive phenomenon which can generate intra-organizational competitive advantage are exposed. Objective To identify the factors of innovation-oriented organizational management, generated by the collaboration of the professional grouping of Kibs companies through the systematization of knowledge, which serve to conceptually delimit the DT phenomenon. Ultimately, it is expected to establish recommendations for this type of companies based on providing services with high knowledge value that strive to digitally transform their businesses. Originality the paper contributes to advancing the conceptual understanding of DT through the study of Kibs companies, which remain understudied. Likewise, there is no known study that analyzes the factors that give rise to DT in a professional grouping of small Kibs companies. It is clear that this union of small companies generates a strong internal capacity for knowledge absorption, through daily interactions with clients and public administrations, which favors the process of implementing certain technological and strategic components that are beneficial for the development of professional activity and increases the propensity to innovate. Methodology qualitative content was analysed using a grounded theory methodology including interviews with experts and the managers of the Kibs companies in the professional sector to obtain a solid basis that can be used to identify the most relevant factors of DT. Findings/results as DT is a multidimensional phenomenon of individual companies, this study presents a conceptual framework for the term with the strategic requirements of the market, organizations, public institutions and technological infrastructures of the professional sector. By considering the disruptive factors of digital development in this macroenvironment, conclusions can be made about the basic principles and effects of DT.